Визначення часу встановлення струму в індуктивному навантаженні перетворювача напруга-струм при негармонічній дії - Василюк, В. Я.; Шклярський., В. І. (Видавництво Львівської політехніки, 2013)
The paper presents analysis of problems dealing with the determination of the current setting time in the inductive component of the complex load of Voltage-to-current (VTC) converter under non-harmonic input influence. There is showed the change in the transient response and in the current setting time of the inductor on changing the VTC converter and complex load parameters. Expression to determine the current setting time of complex load of VTC converter at given level of dynamic error is presented. The estimation of dynamic error in determining the current setting time is presented in accordance with the time dependencies of transient responses of current setting in inductive load of VTC converter with complex load’s and VTС’s converters different parameters. The mathematical model of precision VTC converter [1] with deflection system (DS) of cathode-ray tube (CRT) of television scanning optical microscope connected to its output has been designed and is presented as a complete equivalent circuit taking into account the resistance and parasitic capacitance of load. In accordance with the set conditions of raster formation on screen of such CRT, the control of converter is carried out by non-harmonic signal with variable shape, frequency, amplitude and displacement [2]. Precision VTC converter built as parallel circuit with a deep DS’s current feedback, the signal of which is formed on the feedback resistor, which is connected in series with the load, has been studied. To ensure the aperiodic current setting the bypass resistor is connected to the load in parallel. While analyzing this circuit we’re considering that: the static error due to instability of comparison resistors and feedback resistor is equal to zero, the cutoff frequency of VTC converter is higher than the resonant frequency of the load, and the error due to resistance of DS is compensated. The mathematical model allows to carry out a complete theoretical study of precision VTC converter and to get expressions to determine the parameters upon certain conditions: 1) supply voltage of VTC converter is higher than the maximum voltage on the DS during the transition process; 2) amplifier is presented as one inertial circuit with real parameters: unity gain frequency fВ , gain amplifier K0 ; 3) the resistance of DS rL and parasitic capacitance CL are taken into account at analysis; 4) considered that the feedback resistor RЗЗ is non-inductive; 5) the current flowing through the resistor R2 relative to current of feedback resistor is very small and it is neglected. Розроблено математичну модель прецизійного перетворювача напруга-струм (ПНС), навантаженого відхилювальною системою (ВС), яка забезпечує визначення часу встановлення струму у індуктивній складовій навантаження з необхідною точністю при заданій динамічній похибці. Наведені часові залежності встановлення струму у індуктивній складовій при зміні параметрів ПНС та комплексного навантаження.
Determination of current setting time in inductive load of voltage-to-current converter under non-harmonic influence
Keywords: voltage to current converter; complex load; inductive load; converter speed; accuracy; dynamic error; перетворювач напруга-струм; комплексне навантаження; індуктивне навантаження; швидкодія; точність; динамічна похибка